Image Segmentation by Searching for Image Feature Density Peaks - Zhe Sun; Meng Qi; Jian Lian; Weikuan Jia; Wei Zou; Yunlong He; Hong Liu; Yuanjie Zheng (Applied Sciences, 2018)
Image segmentation attempts to classify the pixels of a digital image into multiple groups to facilitate subsequent image processing. It is an essential problem in many research areas such as computer vision and image processing application. A large number of techniques have been proposed for image segmentation. Among these techniques, the clustering-based segmentation algorithms occupy an extremely important position in this field. However, existing popular clustering schemes often depends on prior knowledge and threshold used in the clustering process, or lack of an automatic mechanism to find clustering centers. In this paper, we propose a novel image segmentation method by searching for image feature density peaks. We apply the clustering method to each superpixel in an input image and construct the final segmentation map according to the classification results of each pixel. Our method can give the number of clusters directly without prior knowledge, and the cluster centers can be recognized automatically without interference from noise. Experimental results validate the improved robustness and effectiveness of the proposed method.